Proceedings of the VI National Meeting of the Italian Group of Paleopathology (GIPaleo) - VV., AA. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
18 giugno 2021Apertura lavori Ore 14:30I SessioneOre 15:15II SessioneOre 17:1019 giugno 2021III SessioneOre 9:00IV SessioneOre 10:55Sessione PosterOre 14:30V Sessione Ore 15:35 VI Sessione Ore 17:30 Chlusura lavori Ore 18:45[read more]